Assessment of The Effect of Long Term Tillage on The Arbuscular Mycorrhiza Colonization of Vegetable Crops Grown in Andisols - Prasetya, Budi; Anderson, Christopher (AGRIVITA, Journal of Agricultural Science, 2011)
In Indonesia, amount of biodiversity could be found including soil microorganism which were useful for sustainable agriculture. Everything lives in agricultural land were interacts and influences each others. Many factors of biotic and a-biotic environment such as land and climate fluctuation influences microbial expansion within the soils. For example arbuscular mycorrhiza (AM) which was formed by myches (fungus) and root of higher plant maybe fluctuated in the expansion due to the soil tillage. Land management and the present higher plant affected its growth and expansion. Mycorrhizae spores as one of the important generative form of various species in the difference host plant. The implication of different host plant often close related to the soil management and properties. Soil sample that was collected from various host plant in the fields or bare land have been found varied spores. Andisols and its properties conserve higher organic matter relatively and developed in the cold temperature, therefore very suitable for AM expansion and also as natural resources stock of AM potentially.Keywords: arbuscular mycorrhiza, andisols, soil tillage, AM colonization